2022
DOI: 10.3390/catal12020116
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-Acetylacetone as an Efficient Source of Superoxide Radicals under Reduced Power Visible Light: Photocatalytic Degradation of Chlorophenol and Tetracycline

Abstract: Visible light-sensitive TiO2-based nanomaterials are widely investigated for photocatalytic applications under high power (≥300 W) UV and visible light. The formation of charge transfer complexes (CTCs) between bidentate ligands and nanocrystalline TiO2 promotes visible light absorption and constitutes a promising alternative for environmental remediation under reduced visible light power. However, the efficiency of photodegradation, the volatilization profile of bidentates, and the role of reactive oxidizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…20,37 However, a higher percentage of ACAC was detected for CTCs calcined under reducing atmospheres (7.4% for hydrogen atmosphere and 5.5% for argon atmosphere) compared to the CTC calcined under static air (3.5%). This result is in accordance with the observation by Almeida et al, 26 who reported that the ACAC fragmentation corresponds to an oxidative process. Therefore, as observed in Figure 3, calcination under reducing atmospheres was expected to lead to the presence of a higher percentage of ACAC in the TiO 2 -ACAC CTC.…”
Section: Xrpd Of Thesupporting
confidence: 93%
See 3 more Smart Citations
“…20,37 However, a higher percentage of ACAC was detected for CTCs calcined under reducing atmospheres (7.4% for hydrogen atmosphere and 5.5% for argon atmosphere) compared to the CTC calcined under static air (3.5%). This result is in accordance with the observation by Almeida et al, 26 who reported that the ACAC fragmentation corresponds to an oxidative process. Therefore, as observed in Figure 3, calcination under reducing atmospheres was expected to lead to the presence of a higher percentage of ACAC in the TiO 2 -ACAC CTC.…”
Section: Xrpd Of Thesupporting
confidence: 93%
“…On the other hand, only one paper that reported TC photocatalytic degradation using CTCs based on TiO 2 was found. In this paper, Almeida et al reported a TC photocatalytic abatement of 68.6% using 200 mg·L –1 of TiO 2 -ACAC 300, a CTC calcined at 300 °C as a photocatalyst, under low-power visible-light excitation (26 W) during 6 h. Nonetheless, to our knowledge, the influence of oxygen vacancies on the photocatalytic performance of TiO 2 -ACAC CTCs has not yet been investigated.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In a contribution by Almeida et al [1], the efficiency of photodegradation, the volatilization profile of bidentates, and the role of reactive oxidizing species (ROS) were explored for nanocrystalline TiO 2 modified with bidentate ligands (acetylacetone). In this study, TiO 2 -ACAC CTC calcined at 300 • C (TiO 2 -A300) was applied for the photocatalytic degradation of chlorophenol (4-CP) and tetracycline (TC) under low power visible light (26 W).…”
Section: Tio 2 -Based Photocatalystsmentioning
confidence: 99%